Ancient Schwannoma of Ansa Cervicalis: A Rare Clinical Entity and Review of the Literature. (8th October 2015) - Rath, Satyajit; Sasmal, Prakash K.; Saha, Kaushik; Deep, N.; Mishra, Pritinanda; Mishra, Tushar S.; Sharma, Rakesh
Abstract : Ancient schwannoma is an uncommon variant of schwannoma, a benign tumor arising from the nerve sheath. It is reported to arise from any nerves except optic and olfactory. However, only six cases of ancient schwannomas arising from ansa cervicalis nerve have been reported to date in English literature. Proper preoperative evaluation is necessary to rule out other causes of neck mass such as thyroid lesions, lymphadenopathy, and carotid body tumor. We report a case of ancient schwannoma arising from the ansa cervicalis nerve. The origin of the lesion from ansa cervicalis was confirmed by intraoperative finding. Postoperative histopathological examination revealed degenerative changes including pleomorphism, cellular atypia, large nuclei with prominent nucleoli, and paucity of mitotic figures. Periphery of the mass showed nuclear palisading with characteristic verocay bodies. Immunohistochemical evaluation for S-100 showed diffuse positivity of the tumor cells, thereby confirming the diagnosis of schwannoma. We consider that schwannoma of cervical region can have origin from any nerve and should try to identify the origin pre- and intraoperatively. The postoperative complications depend on the nerve of origin and the precision of the surgery performed.